Effect of coloured shade nets on yield and quality of pomegranate (Punica granatum) cv. Mridula in semi-arid region of Punjab - MEENA, V S; KASHYAP, POONAM; NANGARE, D D; SINGH, J (The Indian Journal of Agricultural Sciences, 2016)
The productivity of pomegranate (Punica granatum L.) cv. Mridula was examined under shade nets of different colours (Red, Black and Green) with shade intensities (Red 50% PAR, Black 50% PAR, Green 35% PAR and 50% PAR) in Abohar, Punjab over two growing seasons. To overcome the evaporation losses, use of fogger and microsprinkler was done along with Kaolin 4% and Borax 0.4% to prevent sunburn and cracking problem. An insect net (50 mesh) was also used to prevent the damage from insects especially pomegranate fruit fly. The experimental results clearly showed that photoselective nets influenced photosynthetically active radiation (PAR) transmitted through the canopy which caused variation in average monthly temperature and humidity. The quality of the fruits was affected under the open field conditions as compared to other treatments. Maximum acidity (0.412%), Vitamin C (13.52 mg/ 100 g), total sugars (13%) and highest antioxidant activity (40.1%) were recorded under open field conditions. Whereas minimum acidity (0.206%), minimum vitamin C (5.80mg/100g), total sugars (6.8%), and total phenols (7.5%) were recorded in the fruits grown under black shade net (50%). On the other hand, the application of shade net had significant impact on the quantitative characteristics. Shading with the net (Red 50%) resulted in the significant increase in the length of the fruits (83.39 mm) along with higher fruit weight (310 g) and highest yield of 6.70 kg/plant as compared to the open field condition (3.14 kg/plant). The results, therefore, demonstrate the potency of photoselective netting (Red colour) for improving the agro-economic performance of horticultural crops especially in harsh climates and arid zones. Placing the red nets over mature plants at intermediate shade levels (35% PAR and 50% PAR) provides higher yield without any detrimental effects on fruit quality.